(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Celem niniejszych rozważań jest przedstawienie roli działalności gospodarczej w funkcjonowaniu fundacji. Działalność gospodarcza jest od końca lat dziewięćdziesiątych jednym z głównych źródeł dochodów większości fundacji. Jest także sposobem realizacji ich zadań statutowych. Działalność użyteczna gospodarczo może być celem powołania fundacji i wreszcie fundację można traktować jako kolejną, obok spółek prawa handlowego, formę prowadzenia tej działalności. This article discusses the issue of business activity in foundation law. The first part of the article presents various fields on which the business activity is present in everyday fuctioning of foundation. Business activity is one of the main sources of foundation’s income, this is also a way to fullfill statutory goals of foundation. The activity that is economically useful can be a statutory goal of foundation and finnally foundation as a law person can be considered as a form of carring out business activity. From that perspective the rules regarding business activity of foundations in Poland had been examinated. The author proposes liberalisation of this regulation by permitting to carry out business activity without any limitations. It has been proven, that this will not influence the legal construction of foundations, as non – profit activity has actually never, even historically been the essence element of foundtion. On the contrary, first foundations were created with the for – profit intentons, that is to preserve and protect private and church fortunes. Inevitable part of this considerations has been dedicated to the regulations of business activity that is carried out by foundations with public benefit organization status. Finally the tax benefits for the organizations that carry out public benefit activity had been presented. As far as present tax regulations are concerned the indication of precise and short term of factually dedicate profit to public benefit activities in order to keep tax exemption has been introduced.